please answer by splitting the middle term
Attachments:
![](https://hi-static.z-dn.net/files/da8/866a284445a548436154ff9995544249.jpg)
Answers
Answered by
0
Answer:
1)9x^2+18x+8
=9x^2+6x+12x+8
=3x(3x+2)+4(3x+2)
=(3x+2)(3x+4)
2)6x^2+17x+12
=6x^2+9x+8x+12
=3x(2x+3)+4(2x+3)
=(3x+4)(2x+3)
Hpe it hlps u
Plss mark me as brainliest
Answered by
0
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/d29/1be2b0302775d9ed1f907191b6e6d45c.jpg)
diyasd8:
Plz mark it as the brainliest
Similar questions
Hindi,
7 months ago
Geography,
7 months ago
Computer Science,
7 months ago
Social Sciences,
1 year ago
Math,
1 year ago
Math,
1 year ago